The Fire Witness - Kepler, Lars (Blue door, 2014)
One girl is dead Detective Inspector Joona Linna has been called to a home for troubled girls, north of Stockholm. A young girl has been brutally murdered, her body arranged in bed with her hands covering her eyes.